Treatment of reactive dyes from water and wastewater through chitosan and its derivatives - Vakili, M. (wiley, 2016)
Adsorption is a technique used to remove dyes from polluted aqueous solutions. In recent years, the use of low-cost adsorbents, such as chitosan, in wastewater treatment has increased. Chitosan is a safe, environmentally friendly and costeff ective substance produced by alkaline de-acetylation(DD) of chitin, which can be used as an adsorbent. Chitosan and its derivatives have attracted considerable attention as an appropriate adsorbent for dye removal due to their specifi c characteristics such as non-toxicity, cationicity, biodegradability and high absorption capability. Many chitosan derivatives have been obtained by chemical and physicalmodifi cations of raw chitosan, including cross-linking and graft ing new functional groups on the chitosan backbone to absorb dyes. Th is review summarizes the applications of chitosan and its graft ed and cross-linked derivatives in removing dyes from wastewater. It also highlights notable examples in the use of chitosan and its derivatives for dye removal from aqueous solutions. Â© 2016 Scrivener Publishing LLC.